FRAMING NEWS OF PAPUA ARMED CRIMINAL GROUP (KKB) CONFLICT ON KOMPAS.COM - Mayelus D Bastian; Rosalina Wetu (Jurnal Scientia, 2023)
This study aims to see how the Kompas com online media frames news about the Papuan KKB conflict in seven news stories in July 2022. This research was conducted using the Robert N. Entman framing analysis method with a descriptive qualitative approach through its four elements, namely, define problems, diagnose causes , make moral judgments, and treatment recommendations. Methods of data collection is done by means of observation and documentation. This research was conducted by observing the news of the Papuan KKB conflict on online media Kompas.com for the period July 15-21 2022. Furthermore, the news was documented from the Kompas.com news portal. From the results of the research obtained it shows that of the 7 published news, there are 4 news containing the opinions of political figures related to the violent conflict of the KKB in Papua addressed to the Government of Indonesia. The government is asked to pay attention to and resolve the violent conflict that occurred in Papua. The online media Kompas.com frames the seven news about the Papuan KKB conflict which tend to point to the interests of the Papuan people in general. Kompas.com framing the news on the KKB conflict brings the public's view of the government's efforts to deal with and overcome criminal problems in Papua and the government's efforts to rebuild Papua.